2016
DOI: 10.1039/c6ra14918a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, functionalization, characterization, and in vitro evaluation of robust pH-sensitive CFNs–PA–CaCO3

Abstract: The preparation, characterization, and application of Papain (PA) conjugated CaCO3-coated cobalt ferrite nanoparticles (CFNs–PA–CaCO3) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The cells were incubated with 7.8, 15.6, 31.2, 62.5, 125, 250, 500, and 1000 μg Fe/mL of each CFNs, CFNs@PEG, and CFNs@PEG‐FA for 24 h. As shown in Figure , after 24 h of incubation with CFNs@PEG and CFNs@PEG‐FA, the viability of both cell types were still >70% at all incubation concentrations. The results are in agreement with those in the literature . CFNs@PEG and CFNs@PEG‐FA showed decreased toxicity levels even at 1000 μg/mL, but when bare CFNs were present lower cell viability was observed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The cells were incubated with 7.8, 15.6, 31.2, 62.5, 125, 250, 500, and 1000 μg Fe/mL of each CFNs, CFNs@PEG, and CFNs@PEG‐FA for 24 h. As shown in Figure , after 24 h of incubation with CFNs@PEG and CFNs@PEG‐FA, the viability of both cell types were still >70% at all incubation concentrations. The results are in agreement with those in the literature . CFNs@PEG and CFNs@PEG‐FA showed decreased toxicity levels even at 1000 μg/mL, but when bare CFNs were present lower cell viability was observed.…”
Section: Resultssupporting
confidence: 92%
“…The method used to synthesize the core material (CFNs) was conventional co‐precipitation. Fe(NO 3 ) 3 ·9H 2 O (98.5%, Merck) and CO(CH 3 COO) 2 ·4H 2 O (99%, Merck) were used to synthesize cobalt ferrite according to the methodology published earlier . Eventually, the precipitates were finely powdered by grinding to obtain the particles identified as CFNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, another study showed good intracellular drug distribution and interaction for doxorubicin-SPIONs on MCF-7 cells in comparison with a solution of neat doxorubicin. 34 Recently, Nasiri et al 35 showed that the cytotoxic effect was improved in papain-conjugated cobalt ferrite nanoparticles compared to neat papain. Similarly, Mosafa et al 36 demonstrated the identical characteristics of papain-immobilized magnetic nanoparticles compared with neat papain.…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization of the obtained silver microflakes with the APTMS coupling agent was performed based on a previously reported method. In a typical procedure, silver microflakes were uniformly dispersed in anhydrous toluene via sonication followed by the addition of APTMS (1 mM). After stirring overnight at room temperature, the functionalized silver microflakes (denoted as f Ag) were collected and thoroughly washed with ethanol to remove any unreacted APTMS and dried in an oven at 60 °C for 12 h. Functionalized Ag samples 0.1f Ag and 0.01f Ag were also made by using lower concentrations of APTMS (0.1 and 0.01 mM, respectively).…”
Section: Methodsmentioning
confidence: 99%